Co-design of low-profile leaky-wave-fed transmit-array antennas using the generalized Risley prism concept for side-lobe reduction - Matos, S. A.; Fernandes, M.; Felício, J. M.; Costa, J. R.; Fernandes, C. A.; Fonseca, N. J. G. (IEEE Transactions on Antennas and Propagation)
Emerging millimeter wave communications systems require compact, low-mass, low-cost, and energy-efficient antennas, capable of high-gain, wide-angle beam steering. Recent advances in mechanical beam-scanning techniques make them attractive for the above requirements, compared to the phased array antennas, but are still bulkier. A leaky-wave-fed transmit-array (TA) antenna with two-dimensional (2D) beam scanning based on the Risley prism concept (RP), with coaxial rotation of the planar feed and the TA, is a promising approach for reducing the antenna profile to about 1-2?, while maintaining a good beam scanning performance, comparable to other planar solutions. However, these structures suffer from the same side-lobe (SLL) level limitation known for the spatially fed RPs. Another problem is the efficiency/complexity of the feeding antenna, which may limit antenna height reduction. To mitigate these impairments, we propose a novel co-design approach for the feed and the TA structures, enabled by the recent generalized Risley prism formulation. It allows using a Radial Line Slot Antenna (RLSA) both as the leaky-wave feed and first prism efficiently, thus benefiting from its simplicity and beam-forming flexibility. As an example, the TA is implemented as a perforated 3D-printed dielectric slab, which favors a large bandwidth, with 206 mm diameter and 2?; total thickness (1 mm prism separation). It steers the beam up to 58° over 360° azimuth, with SLL below -15 dB, scan loss below -4.0 dB, and 29.3 dBi maximum gain at 29 GHz. The full-wave results were validated experimentally. The proposed formulation is generic, not tied to this example.